A nonhuman primate model of human non-suicidal self-injury: serotonin-transporter genotype-mediated typologies - Wood, Elizabeth K; Kruger, Ryno; Day, Jaclyn P; Day, Stephen M; Hunter, Jacob N; Neville, Leslie; Lindell, Stephen G; Barr, Christina S; Schwandt, Melanie L; Goldman, David; Suomi, Stephen J; Harris, James C; et al. (Neuropsychopharmacology (New York, N.Y.), 2022)
While non-suicidal self-injury (NSSI) occurs in the general population at a surprisingly high rate, with higher rates among certain clinical  populations, its etiology is not well-understood. Consequently, the DSM-5 lists NSSI as requiring further research. This study utilizes a translational model of naturally-occurring NSSI to assess the role of early parental neglect and variation in the serotonin transporter genotype (5-HTT) in the etiology of NSSI. Subjects (N = 161) were rhesus macaques (Macaca mulatta) reared in one of three conditions (mother-reared (MR), peer-reared (PR), or surrogate peer-reared (SPR)), and classified as NSSI (n = 18) or non-NSSI (n = 143). Subjects were genotyped for 5-HTT and their behaviors were recorded during an ecologically-meaningful, stress-evoking, intruder paradigm. Two weeks prior to testing, blood samples were obtained and assayed for plasma cortisol and adrenocorticotropic hormone (ACTH) concentrations. NSSI subjects were more likely to be SPR, paralleling human studies showing that individuals that exhibit NSSI tend to have experienced abuse or neglect early in life. Results also indicated that variation in the 5-HTT genotype differentiated the NSSI subjects. NSSI subjects that were homozygous for the L allele exhibited high plasma ACTH and high rates of stress-induced stereotypies; whereas NSSI subjects with the s allele exhibited impulsive behaviors, including frequently approaching the potentially dangerous intruder, high rates of aggressive vocal threats, and more activity. These results suggest that there may be different 5-HTT genotype-mediated NSSI typologies and that both early experiences and variation in the 5-HTT genotype may be important factors in understanding the etiology of NSSI.